An introduction to criminological theory - Burke, Roger Hopkins
"This book provides a comprehensive and up-to-date introduction to criminological theory for students taking courses in criminology at both undergraduate and postgraduate level. The text is divided into five parts, the first three addressing ideal type models of criminal behaviour the rational actor, predestined actor, and victimised actor models. The fourth part discusses integrated theories from within and across model boundaries and the final part discusses theories in the postmodern condition. Within these the various criminological theories are located chronologically in the context of one of these different traditions, and the strengths and weaknesses of each theory and model are clearly identified. The new edition features comprehensive coverage of recent developments in criminology including situation action theory, desistance theory, peacemaking criminology, as well as Loc̐ Wacquant's thesis of the penal society. Pedagogical features include chapter summaries, critical thinking questions and a full glossary of terms and theories"--